2015
DOI: 10.2337/db14-1772
|View full text |Cite
|
Sign up to set email alerts
|

Forced Hepatic Overexpression of CEACAM1 Curtails Diet-Induced Insulin Resistance

Abstract: Carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) regulates insulin sensitivity by promoting hepatic insulin clearance. Liver-specific inactivation or global null-mutation of Ceacam1 impairs hepatic insulin extraction to cause chronic hyperinsulinemia, resulting in insulin resistance and visceral obesity. In this study we investigated whether diet-induced insulin resistance implicates changes in hepatic CEACAM1. We report that feeding C57/BL6J mice a high-fat diet reduced hepatic CEACAM1 leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
108
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 47 publications
(116 citation statements)
references
References 51 publications
8
108
0
Order By: Relevance
“…Normal acute-phase insulin release to glucose and intact -cell function support the observation that chronic hyperinsulinemia is mainly driven by impaired insulin clearance in Cc1 / mutants (15). Studies in mice (17), dogs (18), and humans (19) demonstrated that defective hepatic insulin clearance is involved in diet-induced insulin resistance. Providing a Western-style diet caused rapid hepatic insulin resistance in healthy young South Asian men but not Caucasians, in association with altered insulin clearance in the Asian group (19).…”
Section: Ex Vivo Palmitate Oxidationmentioning
confidence: 71%
See 2 more Smart Citations
“…Normal acute-phase insulin release to glucose and intact -cell function support the observation that chronic hyperinsulinemia is mainly driven by impaired insulin clearance in Cc1 / mutants (15). Studies in mice (17), dogs (18), and humans (19) demonstrated that defective hepatic insulin clearance is involved in diet-induced insulin resistance. Providing a Western-style diet caused rapid hepatic insulin resistance in healthy young South Asian men but not Caucasians, in association with altered insulin clearance in the Asian group (19).…”
Section: Ex Vivo Palmitate Oxidationmentioning
confidence: 71%
“…Providing a Western-style diet caused rapid hepatic insulin resistance in healthy young South Asian men but not Caucasians, in association with altered insulin clearance in the Asian group (19). We have shown that high fat (HF) reduced hepatic CEACAM1 level by >60% and impaired insulin clearance in WT mice within 3 weeks to introduce metabolic abnormalities that were prevented by forced transgenic fat-inducible CEACAM1 overexpression in liver (17). The clinical implication of our studies is underscored by the observed low hepatic CEACAM1 level in obese, insulinresistant subjects with fatty liver disease (20).…”
Section: Ex Vivo Palmitate Oxidationmentioning
confidence: 94%
See 1 more Smart Citation
“…Of note, CEACAM2 is expressed in the kidney but not liver (4,29). Whether it plays a role in renal insulin clearance is not known but, given that insulin clearance occurs mostly in the liver where CEACAM1 expression dominates, insulin clearance is not expected to be directly affected by Ceacam2 deletion, and elevation in insulin clearance in Cc2 Ϫ/Ϫ mice would be mediated by CEACAM1 phosphorylation in response to insulin in liver (8 -10) as well as kidney (36).…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40] Moreover, correlations of NASH-associated CpG sites with mRNA expression of CEACAM1, SH3BP4 (encoding transferrin receptor-trafficking protein), and NAT2 also support a role for our findings relating differential DNA methylation in NASH with impaired insulin signaling/action. [41][42][43][44][45][46][47] The mechanisms that could alter DNA methylation in the insulin-resistant liver remain to be elucidated. However, these differences in methylation may be due to altered levels of enzymes responsible for adding or removing methyl groups to the genome, such as DNMTs.…”
Section: Discussionmentioning
confidence: 99%